Endorsers and ethnicity in brand imaging for selected retail brands - Santos, Randolph C., Jr (College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT This research documented how local retail clothing brands changed their brand imaging through their use of endorsers by shifting from hiring local models and celebrities, to anonymous models, particularly Caucasians, of other ethnic origins. This led to the hypothesis that local retail brands use ethnicity in their brand imaging in order to position themselves within a transnational market.